Radial variations of wood different properties in Diospyros lotus - Kiaei, Majid; Bakhshi, Reza (Forest Systems, 2014)
Aim of study: The aim of this study was to determine some of the physical, biometry and mechanical strength properties of Diospyros lotus L. wood along radial direction from the pith to the bark and the relationship between wood various properties. Area of study: The study area is located in north Iran in the province of Mazandarn. Material and methods: Testing samples were taken at breast height of tree stem and three radial position of stem radius to determine physical (basic density), fiber biometry (fiber length, fiber diameter, cell-wall thickness) and mechanical properties (modulus of rupture and modulus of elasticity).Main results: The results of ANOVA indicated that there are significant differences along radial direction in above mentioned properties for persimmon wood. Basic density, fiber length, fiber diameter, cell-wall thickness, modulus of elasticity and modulus of rupture increased along radial direction from pith toward the bark. Research highlights: The persimmon wood isn’t suitable for pulp and paper production due to the unfavorable flexibility and Runkel coefficients.Keywords: Diospyros lotus; basic density; fiber features; modulus of rupture; modulus of elasticity.